Pendampingan Menulis Kreatif bagi Remaja di Parangmenang Ponorogo untuk Meningkatkan Kompetensi Literasi - Lisma Meilia Wijayanti; Kunti Nadiyah Salma (CV Edujavare Publishing, 2024)
This community service program aimed to enhance the literacy competence of adolescents in Parangmenang Village, Ponorogo Regency, through a creative writing mentoring program. Literacy, particularly productive literacy skills such as writing, plays a crucial role in developing critical thinking, creativity, and self-expression among young people. However, preliminary observations indicated that adolescents in the village had limited opportunities for structured writing practice and lacked confidence in expressing ideas in written form. To address this issue, a participatory and empowerment-based mentoring approach was implemented. The program involved 20 adolescents aged 13–18 years and was conducted in four main sessions over one month. Activities included an introduction to literacy and creative writing concepts, idea exploration through brainstorming and free writing techniques, guided writing practice, revision, and presentation of participants’ work. Data were collected through participatory observation, analysis of participants’ written products, and reflective discussions. The results showed significant improvements in participants’ ability to develop ideas systematically, organize narrative structures more coherently, and use more varied and communicative language. In addition, participants demonstrated increased motivation, self-confidence, and willingness to share their writings publicly. The program also contributed to the establishment of a small youth literacy group to ensure sustainability. Overall, the mentoring program proved effective in strengthening adolescents’ literacy competence and fostering a productive literacy culture at the community level.